Innovation and the Development of the Canadian Wine Industry - Lord-Tarte, Evelyne (Université d'Ottawa / University of Ottawa, 2012)
This thesis explores the innovation and development of the Canadian wine industry. The main objectives are to present the key development factors, innovation, and collaborations, with particular emphasis on collaborations with higher education institutes. It also empirically assesses the extent to which there are differences among the wine producing regions of British Columbia, Ontario and Quebec. The empirical analysis is based on a firm-level survey of 146 firms. The results show that the Canadian wine production is highly innovative and knowledge intensive. Despite that the wine industry in Canada has developed differently according to its regional context, the pattern of innovation is rather similar among firms.
Keywords: Innovation; Canada; rural development; small wineries; wine industry; collaboration